2021
DOI: 10.3390/polym13030328
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Behavior of Blends of Metallocene Catalyzed Long-Chain Branched Polyethylenes. Part I: Shear Rheological and Thermorheological Behavior

Abstract: Long-chain branched metallocene-catalyzed high-density polyethylenes (LCB-mHDPE) were solution blended to obtain blends with varying degrees of branching. A high molecular LCB-mHDPE was mixed with low molecular LCB-mHDPE at varying concentrations. The rheological behavior of those low molecular LCB-mHDPE is similar but their molar mass and molar mass distribution are significantly different. Those blends were characterized rheologically to study the effects of concentration, molar mass distribution, and long-c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 73 publications
(142 reference statements)
0
6
0
Order By: Relevance
“…The macromers are then efficiently enchained intra-molecularly at the Ni coordinated by the (SO 2 )FI ligand fragment. Repeating this cycle yields high molar mass LCB polyethylenes up to 11 LCB/1000C, as determined by 13 C NMR analysis. It is interesting that in comparison, the tandem monometallic (CF 3 )FI-Ni + (SO 2 )FI-Ni catalytic system produces a bimodal mixture under the same reaction conditions.…”
Section: Bimetallic Catalytic Systemsmentioning
confidence: 94%
See 4 more Smart Citations
“…The macromers are then efficiently enchained intra-molecularly at the Ni coordinated by the (SO 2 )FI ligand fragment. Repeating this cycle yields high molar mass LCB polyethylenes up to 11 LCB/1000C, as determined by 13 C NMR analysis. It is interesting that in comparison, the tandem monometallic (CF 3 )FI-Ni + (SO 2 )FI-Ni catalytic system produces a bimodal mixture under the same reaction conditions.…”
Section: Bimetallic Catalytic Systemsmentioning
confidence: 94%
“…[74] In a similar study, two nonmetallocene catalysts; difluoro-substituted 2,6-bis(imino) pyridyl Fe/MMAO as the oligomerization catalyst and mono 𝛽-diiminato titanium complex/MMAO as copolymerization catalyst were used to convert ethylene as the sole monomer feed to branched polyethylene. [75] In both studies, which were conducted in a single reactor following a simultaneous approach, 13 C NMR spectra revealed that by increasing the molar ratio of oligomerization/polymerization catalyst, the number of ethyl, butyl, and long (≥6C) branches per 1000 carbon atoms increase and the melt temperature shifts into lower temperatures as measured by DSC, accordingly. Miller and coworkers reported a variation of LCB density in the range of 14-21 LCB/1000C.…”
Section: Tandem Catalytic Systemsmentioning
confidence: 99%
See 3 more Smart Citations